Malaysia : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report, 2022)
Malaysia's economy is showing signs of a gradual yet steady recovery thanks to the authorities' impressive vaccine rollout, swift and coordinated implementation of multi-pronged support measures. The recovery nevertheless remains uneven and the output gap sizeable, with significant downside risks. Going forward, the authorities should calibrate macroeconomic policies to the pace of the recovery, while preserving policy space given pandemic-related uncertainties, and simultaneously accelerate structural reforms.